KETERLIBATAN ORANG TUA DALAM BELAJAR : IMPLIKASI TERHADAP PRESTASI BELAJAR SISWA - Lailatul Khasanah; Ika Ratih Sulistiani; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
In achieving positive learning achievement, the involvement of parents in learning is very necessary. This study aims to determine the effects of parental involvement on student achievement. The research was conducted using correlational quantitative methods. The number of respondents studied was 48 students with details of 58% male and 42% female. The results of the trend score analysis showed that the score of parental involvement in student learning was in the high category with an ideal mean (Mi) of 51.5 and an ideal standard deviation (Sdi) of 5.5, it was found that a mean of 57.00 was at high criteria (> 53). The average score of student achievement falls into the medium category with an average report card score of 80 from 7 subjects. Based on the results of the calculation correlation hypothesis test using SPSS 20, there is a significant correlation between the involvement of parents in learning and student achievement of (p value = 0.000) and there is a positive relationship between parental involvement and student achievement (R = 0.512) 51 %. It can be concluded that the involvement of parents in learning has a very important influence on student achievement.